Evaluasi Usability dan Perbaikan Antarmuka Pengguna Aplikasi Mobile Malang Menyapa Menggunakan Metode Usability Testing - Dhiki Sekti Wibawa; Yusi Tyroni Mursityo; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Malang Menyapa is a tourism information application for Malang City based on Android Mobile, developed by the Malang City Culture and Tourism Office. Based on a study conducted by researchers of user reviews on the Google Play Store, Malang Menyapa application has usability issues including the use of background that is too crowded, the design used is still too old school, the colors are too flashy, the content design is not representative, the use of fonts is too much, and less user friendly. Therefore, it is necessary to evaluate and improve user interface design to increase its usability value using the usability testing method. Usability testing is a process that employs people as test participants who represent the target audience to evaluate the extent to which a product meets certain usability criteria. The usability aspects measured in this study are in accordance with ISO 9241-11 namely effectiveness, efficiency and user satisfaction. The usability testing process includes testing tasks, giving questionnaires, and interviews. Based on the results of the interview, found as many as 30 usability problems that will be corrected using 28 compilation guidelines. The results of the effectiveness value measured using completion rate increased from the initial design which was only 78% to 100% for design improvement, the value of efficiency that was measured using overall relative efficiency increased from the initial design ie 82.26% to 100% for design improvement, and the value of satisfaction users measured using the System Usability Scale (SUS) questionnaire increased from the initial design of 27.88 to 81.75 for the design improvement. The results of the application design improvement Malang Menyapa can prove that it can improve the usability problems found.